Evaluasi Penggunaan Obat Diare pada Pasien Anak di Instalasi Rawat Inap Rumah Sakit Dokter Hafiz Cianjur: Evaluation of the Use of Diarrhea Drugs in Pediatric Inpatient at Dr. Hafiz Cianjur Hospital - Ikmal Abdul Lutfi; Fifi Agustari; Julia Totong (Jurnal Ilmiah Farmasi Indonesia (JIFIN), 2024)
Diarrhea is an increase in the frequency and decrease in the consistency of bowel movements compared to a person's normal bowel pattern. Diarrhea is the second cause of death in children under five, and is responsible for the deaths of 370,000 children in 2019. The aim of this research is to evaluate the appropriateness of drug use in pediatric diarrhea patients for the period January – December 2022 at the Doctor Hafiz Cianjur Hospital Inpatient Installation. This research uses non-experimental methods accompanied by an observational descriptive analysis design based on retrospective data from patient medical records. The results of research based on the characteristics of pediatric diarrhea patients showed that the majority of patients were male, 74 people (74%), with an age range of 2-5 years, 82 people (82%). Zinc therapy (32.78%) and probiotics (32.78%) were the most widely used pharmacological therapies for patients. The percentage of correct use of medication consists of correct indication (97%), correct drug (97%), correct patient (100%), correct dose (100%), and correct prescription according to Cross Diarrhea guidelines from the Indonesian Ministry of Health (100%). The length of hospitalization for patients diagnosed with diarrhea accompanied by dehydration and infection was the longest (4.8 days). Patients diagnosed with diarrhea with dehydration had a shorter hospital stay (4.2 days). And patients diagnosed with diarrhea without dehydration had the shortest hospitalization time (3.5 days).